The Change Of The Auditor Towards The Big Four Auditing Firms In Mexico - Toscano Moctezuma, Juan Alfonso; García Benau María Antonia (Advances in Social Sciences Research Journal, 2018)
In this paper, we present the results of an empirical study which analyzes the reasons why some companies with certain corporate characteristics, after having changed their external auditor, choose one of the Big Four auditing firms in Mexico. For this purpose, we have estimated a logistic regression model, using an observable sample of 972 annual reports, belonging to a total of 135 companies listed on the Mexican Stock Exchange, during the period from 2000 to 2007. The results indicate that the reputation of the external auditor, the quality of the audit, the brand of the audit firm and the size of the external auditor, are some of the reasons why some companies with certain corporate characteristics, after having changed their external auditor, choose one of the Big Four auditing firms in Mexico, better known in the business world, such as the “Big Four”.